Neonatal blood transfusion practices in India: a nationwide survey of clinicians - Kolkur, Karthik S.; Patnaik, Suprabha K.; Malshe, Nandini; Deshmukh, Vikrant; Tripathi, Shalini; Nagar, Nandini; Sreekantha, Sreevidya; Suryawanshi, Pradeep (Frontiers in Pediatrics, 2025)
BackgroundBlood transfusion, a vital procedure in neonatal intensive care units (NICUs), also poses risks such as necrotizing enterocolitis, intraventricular hemorrhage, and death. We conducted a nationwide survey to evaluate current neonatal transfusion practices among clinicians in India.MethodsA cross-sectional survey with a structured 23-item questionnaire was conducted online using Google Forms during February 2024. The questionnaire covered key elements of transfusion practices, including threshold, dosing, and duration of blood product administration. Five hundred forty clinicians working in NICUs across India were invited to participate in the survey.ResultsResponses were received from 368 clinicians, most of whom practice in Level 3 Neonatal Intensive Care Units. Approximately 67% reported adherence to the guidelines established by the National Neonatal Forum of India 2020. Packed red blood cells were predominantly transfused at a volume of 15 mL/kg (79%) over a duration of four hours (69%), with a hemoglobin threshold of 7.5 g/dL (48%) employed after two weeks of life in stable preterm neonates younger than 32 weeks. The majority of practitioners (59%) did not utilize diuretics, and half (50%) withheld feeds during red blood cell transfusions. Platelet transfusions were most frequently administered at 10 mL/kg (51%) over a period of 0.5 h (60%), with a threshold platelet count of 50,000/µL in cases of bleeding (60%) or 25,000/µL in the absence of bleeding (58%). Fresh frozen plasma was used in neonates presenting with coagulopathy and bleeding (73%) and also in cases without bleeding (25%), most commonly at 10 mL/kg (47%) administered over 1 h (43%).ConclusionTransfusion practices varied across Indian NICUs despite adherence to NNF guidelines and generally adopting a restrictive approach. The standardization of protocols and enhancement of compliance could potentially improve clinical outcomes and diminish complications associated with transfusion.